2018
DOI: 10.2147/tcrm.s149236
|View full text |Cite
|
Sign up to set email alerts
|

Minodronate for the treatment of osteoporosis

Abstract: Minodronate is a third-generation bisphosphonate that was developed and approved for clinical use in osteoporosis therapy in Japan. The mechanism of action for suppressing bone resorption is the inhibition of farnesyl pyrophosphate synthase, a key enzyme in the mevalonic acid metabolic pathway of osteoclasts, to induce apoptosis of the cells. Minodronate is the strongest inhibitor of bone resorption among the currently available oral bisphosphonates. Large randomized, placebo-controlled, double-blind clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…Kendler et al reported that transition to denosumab produces greater increases in BMD at all measured skeletal sites and a greater reduction in bone turnover than continued alendronate [29]. In this study, we first revealed that switching from MIN, which is a third-generation bisphosphonate and much more active for the inhibition of bone resorption than alendronate or risedronate [30][31][32], to denosumab showed similar beneficial effects on BMD and bone turnover markers. Since MIN is one of the most widely used bisphosphonates in Japan [15], establishing clinical evidence for switching therapy from MIN would benefit patients.…”
Section: Discussionmentioning
confidence: 63%
“…Kendler et al reported that transition to denosumab produces greater increases in BMD at all measured skeletal sites and a greater reduction in bone turnover than continued alendronate [29]. In this study, we first revealed that switching from MIN, which is a third-generation bisphosphonate and much more active for the inhibition of bone resorption than alendronate or risedronate [30][31][32], to denosumab showed similar beneficial effects on BMD and bone turnover markers. Since MIN is one of the most widely used bisphosphonates in Japan [15], establishing clinical evidence for switching therapy from MIN would benefit patients.…”
Section: Discussionmentioning
confidence: 63%
“…However, an animal experiment performed by Naito et al [26] showed that treatment with alendronate may halt bone resorption and reduce levels of pain mediators. Compared to other bisphosphonates, the unique mechanism of action of minodronate on the inhibition of the P2X(2/3) receptor is advantageous, especially in reducing back pain among patients with osteoporosis [27]. However, in the present investigation we did not use minodronate.…”
Section: Discussionmentioning
confidence: 77%
“…A high percentage of patients (87.9%) in Japan received OP medications soon after their high-risk diagnosis, with bisphosphonates, selective estrogen receptor modulators, and teriparatide being the predominant treatment options. Tsuyoshi Ohishi et al [28] wrote a review on minodronate, which is a third-generation bisphosphonate that was developed and approved in Japan. High-quality RCTs have revealed an increase in BMD of both the lumbar spine and femoral neck over 3 years of daily minodronate therapy and risk reduction in vertebral fractures over 2 years of therapy (similar to those with alendronate or risedronate).…”
Section: Discussionmentioning
confidence: 99%